2017
DOI: 10.1002/pat.4030
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of textile materials modified with triclosan-loaded polylactide microparticles

Abstract: A convenient and simple method for preparation of commercial nonwovens with antimicrobial properties was elaborated. The process consists in preparation of poly(L-lactide) microspheres (from poly(L-lactide) with M n = 10,560 and M w /M n = 1.39) containing triclosan (5-chloro-2-(2,4-dichlorophenoxy) phenol) and loading them onto the nonwovens. The microspheres were prepared by spray drying (D n = 3.91 μm, D w /D n = 2.43) and oil-in-water emulsification-solvent evaporation method (D n = 5.84 μm, D w /D n = 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Substantial importance in this field is played by PLA composites equipped with antibacterial additivities, in the majority organic bactericides (e.g., ampicillin [ 9 ] chlorhexidine [ 10 , 11 ], ciprofloxacin [ 12 , 13 ], doxycyclin [ 14 ], gentamycin [ 15 ], oflaxin and vancomycin [ 16 ], triclosan [ 17 , 18 , 19 ], and/or curcumin [ 20 ], etc.). Due to an established role of metal nanoparticles in medicine [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the group of increasing importance is PLA-inorganic hybrids [ 34 ], due to their high antibacterial efficiency, simplicity and also low cost of technological preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial importance in this field is played by PLA composites equipped with antibacterial additivities, in the majority organic bactericides (e.g., ampicillin [ 9 ] chlorhexidine [ 10 , 11 ], ciprofloxacin [ 12 , 13 ], doxycyclin [ 14 ], gentamycin [ 15 ], oflaxin and vancomycin [ 16 ], triclosan [ 17 , 18 , 19 ], and/or curcumin [ 20 ], etc.). Due to an established role of metal nanoparticles in medicine [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the group of increasing importance is PLA-inorganic hybrids [ 34 ], due to their high antibacterial efficiency, simplicity and also low cost of technological preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of bacteriostatic zone, to a certain extent, indicates that the added bacteriostatic agent (triclosan) had played a good antibacterial effect. Karaszewska et al(2017) had also found that a wide range of bacteriostatic bands also appeared around the triclosan-loaded polylactide microparticles, based on the same evaluation criteria (ISO 20645 − 2004). Besides, it has a similar results that Cui et al…”
Section: 23mentioning
confidence: 96%
“…In a low concentration of antibacterial research, triclosan's antibacterial performance was manifested in inhibiting bacterial growth and reducing adherence to the polymer. Triclosan as an antimicrobial preparation of textile materials had also showed a good antibacterial effect (Karaszewska et al 2017); (Cui et al 2015); (Peila et al 2013). At present, although lter materials with anti-microbe performance were ordinary, it still lacks the detailed information on the use and e cacy of triclosan as antibacterial agent applied to ventilation lter materials.…”
Section: Introductionmentioning
confidence: 99%
“…Polylactide (PLA) presents polymers of multifunctional application, widely used in medical related areas [1]. PLA hybrids with antibacterial additivities (bactericide agents) provide antiseptic properties, and therefore are applied in a variety of medical applications, namely, such as bioactive fibers for drug delivery [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], for tissue engineering applications [19][20][21][22], forwound healing materials [23][24][25][26] and membranes for efficient treatment of burns [27,28].…”
Section: Introductionmentioning
confidence: 99%